Resilience Building Against Earthquakes in traditional settlements of Kathmandu Valley - Marahatta, Punya Sagar; Pokharel, Jiba Raj (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 4, 2013)
The Kathmandu valley communities have been facing earthquake disasters once in every 75-100 years. The architecture and settlements in Nepal have responded to earthquakes of both small and large magnitude through the use of indigenous technology. Many of them still remain intact to their shape and size. In the last 150 years however, architecture has been increasingly shaped by external influences rather than by local realities. The use of modern construction materials has arguably not abated the increase in physical, social and cultural vulnerability. The paper is the outcome of community-based participatory research. The paper argues that the socio-cultural attributes are key variables in the resilience of communities to these natural disasters.